T asked in Education & ReferenceHomework Help · 2 months ago

simplify (ln e)/6?

3 Answers

Relevance
  • 2 months ago

    Let --

    =>  (ln e)/6  =  x

    =>  ln (e)  =  6 x

    =>  logᵨ e   =  (6 x)

    =>  1   =   6 x  ........  Since logₐ (a)  = 1

    =>  x  =  ( 1/6 ) 

    Hence  (ln e)/6 =  1/6  Answer

    • Commenter avatarLog in to reply to the answers
  • 2 months ago

    log to the base a of a = 1....

    so( ln(e))/6 = 1/6

    • Commenter avatarLog in to reply to the answers
  • 2 months ago

    (ln e)/6

    1/6 <––––––

    • Commenter avatarLog in to reply to the answers
Still have questions? Get answers by asking now.